2018
DOI: 10.1177/0284185118780901
|View full text |Cite
|
Sign up to set email alerts
|

Role of elastography for downgrading BI-RADS category 4a breast lesions according to risk factors

Abstract: Background Elastography has been introduced as an additional diagnostic tool to ultrasonography (US) which helps clinicians decide whether or not to perform biopsy on US-detected lesions. Purpose To evaluate the role of strain elastography in downgrading Breast Imaging Reporting and Data System (BI-RADS) category 4a breast lesions according to personal risk factors for breast cancer in asymptomatic women. Material and Methods Strain elastography features of a total of 255 asymptomatic category 4a lesions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…According to the study by Jieun Koh et al, BI-RADS 4a lesions were classified into "average" and "high" risk by personal or family history, and "soft" and "not soft" by elastography. Only the lesions with "average risk" and "soft stiffness" could be downgraded without further examination [19]. It was found that the missed diagnosis rate for malignant lesions was only 1.5%, and 26.7% (68/255), respectively, and benign nodules could be degraded.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study by Jieun Koh et al, BI-RADS 4a lesions were classified into "average" and "high" risk by personal or family history, and "soft" and "not soft" by elastography. Only the lesions with "average risk" and "soft stiffness" could be downgraded without further examination [19]. It was found that the missed diagnosis rate for malignant lesions was only 1.5%, and 26.7% (68/255), respectively, and benign nodules could be degraded.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies, tissue stiffness is associated with the risk of malignancy; the harder the lesion is, the greater the probability of malignant risk is [16][17][18]. Ultrasound is increasingly used in clinical breast examination and has demonstrated good performance not only in breast tumour differential diagnoses but also for the potential to downgrade BI-RADS 4a lesions to reduce false-positive biopsies without increasing the risk of missing cancers [19].…”
Section: Introductionmentioning
confidence: 99%
“…Most category4a lesions are benign, but may undergo unnecessary biopsies. To better address the tradeoff of 4a lesions, new modalities, such as elastography, have been put into clinical use to lower the false-positive rate 29,30 .And statistically signi cant improvement in the speci city and AUC was acquired for the residents after using S-Detect™ for category 4a lesions, suggesting that a dedicated CAD system might also provide additional diagnostic information. A CAD system could also be an effective method to downgrade benign category 4a lesions, and reduce unnecessary biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…In einer Studie, in der Frauen mit BI-RADS-Klassifikation 4a aufgrund der bekannten Brustkrebs-Risikofaktoren in zwei Gruppen (durchschnittliches Risiko und Hochrisiko) unterteilt wurden, wurden Frauen mit durchschnittlichem Risiko mittels Strain-Elastografie zusätzlich in solche mit weichen und nicht-weiche Läsionen unterteilt. Mit einer Malignitätsrate von 1,5 % in der Untergruppe mit weichen Läsionen ist diese Häufigkeit vergleichbar mit BI-RADS 3 Tumoren [19]. In einer weiteren großen Studie wurde die SWE sowohl zum "Upgrade" von BI-RADS 3 als auch zur Herabstufung von BI-RADS 4a Tumoren verwendet, wodurch die Gesamtspezifität der Untersuchung verbessert wurde, ohne entsprechende Einbußen bei der Sensitivität [11].…”
Section: Elastografie In Der Brustbildgebungunclassified
“…In another study using both strain-and shear-wave imaging, 290 out of 494 BI-RADS 4a tumors were downgraded to BI-RADS 3 with only one malignant lesion incorrectly downgraded [18]. A study using known breast cancer risk factors to stratify women with BI-RADS class 4a in to average risk and high risk patients, strain elastography could additionally subdivide the former group in to a soft and non-soft tumor group with only 1.5 % malignancies in the soft tumor group, making the frequency of malignancies comparable with BI-RADS 3 tumors [19]. In another large study, SWE was used to both upgrade BI-RADS 3 and downgrade BI-RADS 4a tumors thereby improving the overall specificity of the examination without lowering sensitivity [11].…”
mentioning
confidence: 99%